Chemical and mineralogical characterizations of a low-pH cementitious material designed for the disposal cell of the high-level radioactive waste (HLW). (December 2022) - Bonnet, J.; Mosser-Ruck, R.; Sterpenich, J.; Bourdelle, F.; Verron, H.; Michau, N.; Bourbon, X.; Linard, Y.
Abstract: This paper presents the chemical and mineralogical characterizations of a cementitious material and its behaviour to temperature increase in conditions close to those of radioactive waste storage. The formulation, based on a CEM III/C, silica fume, bentonite and hydrotalcite makes a low-pH cementitious grout with a low viscosity. Results show that the mineralogical composition of this material evolves during setting. Two years after setting, it is a macro porous geomaterial, composed of few C-(A)-S-H with a low C/S ratio (<0.4) formed from the blast furnace slags. It also contains well-crystallized ettringite, hydrotalcite, calcite and still non hydrated C2S. In contact with air, a substantial enrichment in calcite and gypsum is observed. The heating up to 90 °C leads to the transformation of the Na-rich smectite of the bentonite into a Ca and/or Mg-rich one and the formation of opal-CT, vaterite and aragonite. Hydrotalcite is stable whereas gypsum and anhydrite disappear.